ANALYSIS OF HYDROXYAPATITE/GELATINE COMPOSITION ON THE FILAMENT FORMATION USING PISTON EXTRUSION METHOD - Tandanu, Yoga A; Santjojo, Dionysius J D H; Masruroh, Masruroh (Universitas Mataram, 2024)
HA/Gelatine bio composite is the main material in making scaffolds that have the advantage of biocompatibility and high biodegradability. One method of making scaffolds is using piston extrusion 3D printing technology, which is compatible with several types of materials, especially HA/gelatine biocomposites. This study aims to determine the effect of HA/gelatine bio composite composition on the filament formation process which is influenced by the rheological properties of the material. The filament extrusion process is influenced by rheological properties in the form of viscosity. The synthesized HA material was then dissolved with gelatin in the ratio of 1:2, 1:3, 1:4, 1:5, and 1:6 homogeneously. After that, viscosity measurements were made on each variation of HA/gelatine composition with a viscometer. The biocomposite solution that has been mixed homogeneously is then extracted until it comes out of the nozzle. Meanwhile, the viscosity of the HA/gelatine bio composite solution when given piston pressure can be known through the calculation process. The viscosity test results show that there is a change in the viscosity of the solution. This is caused by the shear-thickening phenomenon due to the application of pressure on the fluid. Based on the experimental results, the extrusion results still do not form filaments, which indicates that the rheological properties of the HA/gelatine bio composite solution are still too liquid so other material modifications are needed. The extrusion speed of 0.42 mm/s used in this study is too fast for the HA/gelatin material solution, so it has not formed optimal filaments.